INFLUENCE OF SOCIO ECONOMIC FACTORS ON STAPLE FOOD PRODUCTION. A CRITICAL LITERATURE REVIEW - KIMANI, JAMES (Journal of Food Sciences, 2021)
Purpose: Agricultural management practices are key for higher production and are influenced by training as well as financial resources which enable farmers to adopt better practices as well as new farming methods. The general objective of the study was to the study was to establish influence of socio economic factors on staple food production.. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study found out that most of the farmers were marginalized on gender, age and education and still suffers inequalities in the development ladder. Gender inequality is still in existence and plays a major role in placing the women in informal sectors, in limited wages employment activities it is an outstanding factor that plays a major role in food insecurity at house hold level. Land is a major resource for food production and majority of the small scale farmers' occupied land that was self-owned which was less than 1 acre and was not adequate for food production for sustainable food security Recommendations: The study recommends that that the extension services should be improved through retraining of existing extension workers , increasing the number of the extension service providers at farm levels .The government should also increase the facilitation of extension service so as to enable service delivery through training, demonstration , farm visit as well as group trainings amongst other training avenues so as to ensure the farmers are equipped with the right knowledge and technology for staple food production